Left Lung and Pulmonary Artery Hypoplasia: A Rare Case of Hemoptysis - Pinheiro, Maria Guiomar (2021)
Pulmonary hypoplasia or agenesis is a rare congenital disorder that results in lung underdevelopment. This disease is usually found in children but rarely encountered in adults. We describe the case of an 84-year-old woman diagnosed with a unilateral pulmonary hypoplasia presenting simultaneously with left pulmonary artery hypoplasia. Due to this condition, the patient had a lifelong history of pulmonary infections that resulted in several bronchiectases in the affected lung. Moreover, the pulmonary artery hypoplasia led to the development of pulmonary hypertension and collateral circulation causing hemoptysis, giving rise to the patient attending the emergency department. Although we were able to medically manage the hemoptysis, it can be fatal and require surgical intervention. Hence, an early diagnosis is essential so that appropriate follow-up and prompt prevention and treatment of complications, such as pulmonary infections, hemoptysis and pulmonary hypertension, are achieved. Learning points: Although rare and typically associated with childhood, lung and pulmonary artery hypoplasia can in exceptional cases be present in adult life.The diagnosis of lung and pulmonary artery hypoplasia is challenging in adults as they can easily be mistaken for more common diseases.Symptoms and complications may be life-threatening, including dyspnea, hemoptysis, recurrent pulmonary infections and pulmonary hypertension.An early diagnosis is extremely important because it allows a close follow-up with consequent timely detection and treatment of serious complications, especially pulmonary hypertension.